Comparison of the presence and absence of an intervention to reduce hand stereotypies in individuals with Rett syndrome. Issue 2 (28th December 2021) - Hirano, Daisuke; Goto, Yoshinobu; Shoji, Hiroaki; Taniguchi, Takamichi
Abstract: Background: We investigated how many individuals with Rett syndrome were undergoing interventions to reduce stereotypic hand movements and the factors determining the presence or absence of an intervention. Method: A questionnaire was sent to 194 families. Each survey item was compared between the intervention and non‐intervention groups according to the presence or absence of interventions to reduce hand stereotypies. Results: Information was acquired from 72 cases; 72.1% of individuals had received an intervention to reduce stereotypies at some point in their lives. An upper limb splint was the most common intervention. Age, locomotor and reaching function, diagnostic age, frequency and type of stereotypy, joint contractures and stereotypy‐associated problems separated the presence or absence of a current or past intervention. Conclusions: Interventions for stereotypy‐associated problems are important and there are several variables related to whether an intervention is received.